The Influence of Service Quality, Product Quality, and Price on Customer Loyality Throught Customer Satisfaction: A Study of Online Wood Sales at Perhutani Stores in West Java and Banten - Azizah, Atiqah Jilan Nurin; Hidayatullah, Deden Syarif (GoAcademica Research & Publishing, 2025)
The progression of digitization requires commercial entities, especially state-owned enterprises (SOEs), to improve online sales optimization. This study investigates the influence of service quality, product quality, and pricing on customer loyalty, mediated by customer satisfaction, in online wood product sales via Toko Perhutani (PoTP). The sample consisted of 128 active PoTP clients from the Commercial Wood Business Unit in West Java and Banten, obtained by selective sampling. Data were analyzed using PLS-SEM with SmartPLS 4.0. The results demonstrate that the quality of services and products positively affects consumer satisfaction, although does not directly foster loyalty. Customer satisfaction acts as a vital intermediate between service and product quality concerning loyalty, but price significantly impacts loyalty directly, regardless of satisfaction mediation. The results highlight the crucial impact of pricing on consumer loyalty in SOE e-commerce, suggesting that competitive pricing strategies, along with improvements in service and product quality, can promote both satisfaction and loyalty. This study provides theoretical insights into e-commerce consumer loyalty and practical recommendations for Perum Perhutani concerning its digital transformation